Relationship marketing survey in the state civil service: A case study on social welfare department of Sarawak / Belayong Pok - Pok, Belayong (2007)
This study was conducted to identify factors affecting relationship marketing with regard to employee's routine work. This include to identify factors that positively influence relationship marketing activities in the organization. And also to identify problems of relationship marketing role within the department. On top of that, the effectiveness of the major mediums and mode of dessiminating information in the department were also evaluated. There were 96 questionaires had been distributed consensusly. However, only 82 questionaires were successfully collected of which among all are useful sources for data analysis, The respondents were all the current employees of Headquarters, Kuching Divisional, and Samarahan Divisional Social Welfare Office of Sarawak.